Comparison of neuraxial acoustic target window of the spine among rider sitting, cross leg, hamstring stretch, and classical sitting position: An observational study - Govind Singh; Priyanka Sethi; Manbir Kaur; Pradeep Bhatia; Pawan K. Garg; Kamlesh Kumari; Pawan K. Dixit (Journal of Anaesthesiology Clinical Pharmacology)
Background and Aims: To compare ultra-sonographic dimensions of acoustic target window of the spine in the participants at four different sitting positions namely cross leg sitting (CLP), hamstring stretch (HSP), classical sitting (CSP) and riders sitting position (RSP). The primary objective of this study was to measure the neuraxial acoustic target window (defined as interlaminar distance between L3-L4 lamina). The secondary objective was to compare ultra-sonographic measurements of the depth of ligamentum flavum from the skin, and to compare the diameter of intrathecal space and comfort score in the four different sitting positions. Material and Methods: This study is a prospective observational study. Eighty participants were included and positioned in four different sitting positions to perform an ultra-sonographic scan and measure various parameters of the acoustic neuraxial window. The interlaminar distance, the distance of skin from the ligamentum flavum, and the diameter of the spinal canal or intrathecal space was measured in the L3-L4 intervertebral space in different positions. Results: The mean value of interlaminar distance among four sitting positions was ranging from 1.40 cm to 1.44 cm (P value 0.725.) The distance of ligamentum flavum from skin and diameter of intrathecal space was also comparable in all the groups. The comfort score in CSP was significantly better when compared to other groups with a median score of 4 (P value < 0.001). Conclusions: There is no statistically significant difference in interlaminar distance in various sitting positions. All four positions are equally effective and can be used as an alternative to spinal/epidural intervention, but the CSP came out to be the most comfortable and more emphasis should be given to the comfort as it increases the chance of success rate of the procedure.